NFC communication protocol (International Journal of Engineering and Computer Science, 2018)
Near Field Communication (NFC) is a short-range communication technology. Because of its popularity, NFC is widely applied in the field of Internet of Things (IoT). NFC technology reduces the use of many other devices, so that only smartphones, which have NFC embedded in them, are then widely used for various purposes. Smartphones are becoming quite popular equipment today, because smartphone users are increasing from time to time. With this development, NFC is embeded in smartphones widely used and quite popular. Implementation of NFC has been done in various fields, such as health, business, transportation and others. NFC applications in the Service Domain include healthcare, location, finance, social networking, entertainment, education etc. In the field of healthcare applications, NFC can facilitate communication between patients and paramedics, such as doctors, nurses, pharmacists, and other sections. In other fields there are social networking applications, entertainment applications, education applications, NFC miscellaneous applications. In terms of the development of the tag itself, NFC can be discussed with 2 kinds of approach. Firstly is from the side of tag, and secondly is in terms of communication technology. There are 4 types of NFC tags, type 1, type 2, type 3 and type 4. Each type has its own specifications. Frames, data and payload formats have their own different specifications. In its technological side  there are 3 types of NFC A, B and F. Each type has its different way in signals and the data format sent. NFC type A is used in this testingSuch rapid development, however, gives  positive and negative impacts. One of the effects is that with the use of NFC cards that there will be more possibilities for multiple cards to be read simultaneously. For this reason, a reader is required to read more than one card. Trials show that some cards can be read by a reader sequentially and can write or read.